Insomnia among Town Residents in Ethiopia: A Community-Based Cross-Sectional Survey. (2nd May 2019) - Ali, Tilahun; Belete, Habte; Awoke, Tadesse; Zewde, Fisseha; Derajew, Habtamu; Yimer, Solomon; Menberu, Melak
Abstract : Background . Insomnia is one of the most common sleep problems throughout the world and a major public health concern among adults in the general population. The aim of this study was to assess the prevalence of insomnia and its associated factors among town adult residents in Ethiopia. Methods . Community-based cross-sectional study was done among 840 randomly selected adult participants by using standardized and pretested Athens insomnia scale (AIS) to assess insomnia. Systematic random sampling technique was used to get samples of the study participants. Data were entered into Epi-Info and analyzed using SPSS version 20. Descriptive, bivariate, and multivariate logistic regression models were used for analysis. Adjusted odds ratio (AOR) with 95% Confidence Interval (CI) was used to show the odds, and P value < 0.05 was considered as statistically significant. Results . The prevalence of insomnia was found to be 42.9%. Sleep problems were associated with female sex [AOR =2.74, 95% CI; (1.77, 4.24)], age above 48 years [AOR=4.67, 95% CI: (2.32, 9.40)], being single [AOR=2.81, 95% CI (1.59, 4.95)] and widowed [AOR=4.20, 95% CI; (1.60, 11.01)], khat chewing [AOR=1.76, 95% CI; (1.19, 2.60)], current tobacco smoking [AOR=3.13, 95% CI; (1.64, 5.95)], caffeinated beverage use [AOR=1.67, 95% CI; (1.12, 2.49)], comorbid medical-surgical disorders [AOR=2.03, 95% CI; (1.18, 3.48)], common mental disorders [AOR=8.92, 95% CI; (5.93, 13.44)], and noise at bed time [AOR=2.13 95% CI; (1.20, 3.78)]. Conclusion . The prevalence of insomnia has to be found high and associated with many area related factors. It is important to pay attention in urban settings and large scale studies recommended.